1996
DOI: 10.1128/mcb.16.5.2195
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 1 Binds Two Novel Splice Variants of the Regulatory Subunit of Phosphatidylinositol 3-Kinase in Muscle and Brain

Abstract: We have identified two novel alternatively spliced forms of the p85␣ regulatory subunit of phosphatidylinositol (PI) 3-kinase by expression screening of a human skeletal muscle library with phosphorylated baculovirus-produced human insulin receptor substrate 1. One form is identical to p85␣ throughout the region which encodes both Src homology 2 (SH2) domains and the inter-SH2 domain/p110 binding region but diverges in sequence from p85␣ on the 5 side of nucleotide 953, where the entire break point cluster gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
113
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 41 publications
1
113
0
Order By: Relevance
“…In addition, we observed that changes in PI 3-kinase were present in all suicide subjects whether they were diagnosed with major depression or other psychiatric illnesses, which further suggests that these changes are related to suicide rather than some specific psychopathology. A number of studies have shown that all catalytic and regulatory isoforms of class IA PI 3-kinase, except p110d, are highly expressed in the central nervous system (Pons et al, 1995;Antonetti et al, 1996;Fruman et al, 1996;Inukai et al, 1997). When we examined the relative mRNA distribution of catalytic and regulatory subunit isoforms of PI 3-kinase, an interesting pattern of expression emerged in the human PFC and hippocampus.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we observed that changes in PI 3-kinase were present in all suicide subjects whether they were diagnosed with major depression or other psychiatric illnesses, which further suggests that these changes are related to suicide rather than some specific psychopathology. A number of studies have shown that all catalytic and regulatory isoforms of class IA PI 3-kinase, except p110d, are highly expressed in the central nervous system (Pons et al, 1995;Antonetti et al, 1996;Fruman et al, 1996;Inukai et al, 1997). When we examined the relative mRNA distribution of catalytic and regulatory subunit isoforms of PI 3-kinase, an interesting pattern of expression emerged in the human PFC and hippocampus.…”
Section: Discussionmentioning
confidence: 95%
“…(40) Mice lacking only p85a are viable, (41) but mice lacking p85a, p55a, and p50a die immediately after birth, (34) indicating that p55a and p50a can compensate for the loss of p85a in vivo. In addition, PI3K activity is enhanced in mice lacking only p85a compared with wild-type mice, possibly because of higher p50a/p55a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Pik3r1 can be expressed in three splice variants that encode p85a, p55a, and p50a respectively; on the other hand, Pik3r2 and Pik3r3 are known to present only one transcript and encode p85b and p55g respectively. While p85a and p85b are ubiquitously expressed (Gout et al 1992), p50a and p55a are present in fat, muscle, liver, and brain (Antonetti et al 1996, Inukai et al 1996, and p55g is mainly expressed in the brain (Pons et al 1995). All members of the p85 family contain a p110-binding region tethering them to a specific domain located at the N-terminal end of class IA p110s.…”
Section: Two Class I Pi3k Typesmentioning
confidence: 99%